Severe retinal hemorrhages at various levels with a serous retinal detachment in a pediatric patient with aplastic anemia–A case report - Jiang, Xiaoshuang; Shen, Mengxi; Liang, Licong; Rosenfeld, Philip J.; Lu, Fang (Frontiers in Medicine, 2023)
Background: Aplastic anemia can cause ophthalmic abnormalities in patients. Vision loss in a child with aplastic anemia due to massive retinal hemorrhages at various levels is rare. Case Presentation: A pediatric patient with aplastic anemia presented with retinal hemorrhages at multiple levels along with a serous retinal detachment in both eyes and subsequent retinal changes after pars plana vitrectomy. Conclusions: Anemia and thrombocytopenia in aplastic anemia could cause severe retinal hemorrhages and result in retinal atrophy and retinal edema. Vitrectomy can be performed to remove vitreous hemorrhage, but risk factors for retinal atrophy and edema need further investigation.